Safety, immunogenicity, and protective efficacy of the intranasal live pertussis vaccine GamLPV in an infant monkey model (Papio hamadryas) - D. T. Kubrava; A. Yu. Medkova; A. Z. Matua; I. G. Kondzariya; A. A. Amichba; Kh. Z. Trapsh; L. V. Gamgiya; S. G. Kulikov; L. N. Sinyashina; Z. Ya. Mikvabiya; G. I. Karataev (Биопрепараты: Профилактика, диагностика, лечение, 2024)
INTRODUCTION. The current progressive increase in pertussis incidence and infant mortality rates is due to the insufficient effectiveness of existing vaccines, both in Russia and worldwide. Previous clinical trials showed that healthy adult volunteers developed long-term antibacterial immunity after vaccination with GamLPV, an intranasal recombinant live pertussis vaccine developed by the National Research Center for Epidemiology and Microbiology named after the honorary academician N. F. Gamaleya. Further clinical development of GamLPV in paediatric volunteers, including infants, requires preclinical studies in a newborn monkey model.AIM. This study aimed to evaluate the safety, immunogenicity, and protective efficacy of the GamLPV vaccine in infant hamadryas baboons (Papio hamadryas) challenged with pertussis after intranasal vaccination.MATERIALS AND METHODS. The study used 20 hamadryas baboons, including 7 infants aged 1–1.5 months, 7 mothers of these infants, and 6 control animals. The study examined the time course of changes in serum levels of specific IgG antibodies to pertussis toxin (PT) and filamentous haemagglutinin (FHA) by enzyme-linked immunosorbent assay (ELISA), monitored changes in serum levels of Bordetella pertussis antibodies by agglutination immunoassay, and detected B. pertussis DNA in oropharyngeal aspirates by real-time polymerase chain reaction.RESULTS. Intranasal GamLPV administration to infant baboons induced the production of specific IgG antibodies to PT and FHA (ELISA) and an increase in the total pertussis antibody titre (agglutination immunoassay). GamLPV did not cause any injection site or systemic reactions. There were no changes in complete blood counts and serum biochemistry profiles after vaccination. The protective efficacy of GamLPV against B. pertussis was demonstrated in challenge tests, where immunised animals had no clinical signs or laboratory findings indicative of pertussis in contrast to controls.CONCLUSIONS. The study demonstrated the safety and immunogenicity of the intranasal live pertussis vaccine GamLPV in newborn hamadryas baboons. GamLPV shows promise in the primary vaccination of infants, the revaccination of children and adults, and the development of herd immunity against pertussis in families.